Long term levels of bile acids, fibroblast growth factor-19, and glucagon-like peptide-1 after bariatric surgery - Mee Kyoung Kim; Hyuk-Sang Kwon; Ki-Hyun Baek; Ki-Ho Song (Asian Journal of Surgery, 2025)
Objectives: Glucagon-like peptide-1(GLP-1) is a hormone often measured in the short-term following Roux-en-Y gastric bypass (RYGB) due to its elevation and association with improvement of glucose metabolism. We examined the durability of this effect in patients with type 2 diabetes mellitus (DM) in the long term after RYGB. Methods: Obese patients with type 2 DM who had received RYGB 10 years ago (n = 10) were enrolled and a meal tolerance test (MTT) was performed. A matched control group with type 2 DM (n = 5) underwent MTT. Results: Glucose levels during the MTT did not differ between patients with RYGB and the nonsurgical group. Insulin, C-peptide and GLP-1 levels during MTT were significantly higher in patients with RYGB compared with the nonsurgical group (Area under the curve [AUC] of insulin; 57.4 ± 22.9 vs. 27.7 ± 11.1 mIU/L•hr, P = 0.008; AUC of total GLP-1; 189.4 ± 74.72 vs. 52.13 ± 10.23 pM •hr, P = 0.002), and in particular, peak insulin, C-peptide and GLP-1 levels observed 30–45 min after eating were markedly different from those in the nonsurgical group. Bile acids (BAs) and fibroblast growth factor 19 (FGF-19) levels during MTT were higher in patients with RYGB compared with the nonsurgical group. Peak BAs and FGF-19 levels tended to be higher in the RYGB. Conclusions: An enhanced GLP-1 response was noted 10 years after RYGB, strongly suggesting a durability of this effect. BAs and FGF-19 were increased in the RYGB group, but not as much as the pronounced increase in GLP-1 secretion.